MP3 PLAYER APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 INTERFACE WITH WINDOWS MEDIA PLAYER FORMAT - Supriyono Supriyono; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2002)
Multimedia technology, MP3 (MPEG Audio Layer-3) is someone that a storage ofmusic in digital form offers many advantages compared to analog form. MP3 Playeris a media used for computer users who like the music, especially MP3.MP3 is a digital audio compression standard developed by the Institute and ThomsonMultimedia Freunhofer. With MP3, a digital music that can be encoded into a tenkaliatau reduced in size even more by simply reducing the existing sound quality.Although the interface of Windows Media Player or other MP3 player applications,such as Winplay, Winamp, Sonique existing reatif easy to play MP3 music, but tocome up and read the important information from an MP3 file, such as song title,artist name, album name and when the song was made it was not easy.MP3 Player application was made to write a program using Microsoft Visual Basic6.0 supported 64-bit memory and Windows 98 Second Edition installed first.The advantage of MP3 Player is able to display and read the important informationfrom an MP3 file and can specify the duration songs or old songs.